Roles of Women in Living Income: Coping Strategies and Perception of Waste Collectors in Battambang Town, Battambang Province - Koy, Phearun; Serey, Mardy (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This research study aims to explore the specific roles women play in this field, the disparities they face compared to men, and their coping mechanisms. Methodology: A mixed-methods approach was used for this research, combining quantitative data from household surveys and desk reviews with qualitative data from key informant interviews. The study reviewed relevant research papers, articles, and reports, including project progress reports, published journals, guidelines and policies related to waste collection, and research reports from other researchers and policymakers. Main Findings: The research findings revealed that women's family status significantly impacts their economic decisions, often leading them to work for pay to support their families. Household surveys showed that women comprised 64% of respondents, and 54% had no schooling. Additionally, 37% of respondents were aware of women's roles in providing for their families, while key informant interviews with community organizations confirmed this understanding. While the study found that 60% of respondents believed that increased women's rights would not compromise men's rights, 40% disagreed. Some respondents expressed concerns about men losing their privileges if women gained more rights. However, the study concluded that women's contributions to household income should be valued more, and that collaborative efforts are needed to achieve gender empowerment and economic management. Novelty/Originality of this study: Through this research, the master plans for solid waste management will be developed and the partnership with private sector will be strengthened to improve waste management practices and increase income for waste collectors.